Radiation resistant sealing material for photolithography processes and method for producing same

By introducing perfluoroalkyl iodide terminators into the sealing material to terminate the free radicals of the fluororubber chain, the problems of radiation resistance and low particle release in sealing materials for semiconductor devices are solved, realizing the preparation of high-performance, low-cost sealing materials suitable for semiconductor devices at 7nm and below nodes.

CN122628459APending Publication Date: 2026-08-25ANHUI DUOKEN INNOVATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610798736.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-04
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing sealing materials cannot effectively prevent free radical chain degradation caused by high-energy plasma and ultraviolet radiation in dry plasma etching and EUV lithography equipment for semiconductor processes of 7nm and below, resulting in particle release and premature failure. Moreover, they are costly and difficult to apply on a large scale.

Method used

Perfluoroalkyl iodides are used as radical chain transfer terminators. Iodine radicals (I·) are preferentially released through homolytic cleavage of CI bonds with specific structures under plasma radiation, terminating the free radicals of fluororubber chains. Combined with bisphenol AF and BPP vulcanization systems, radiation resistance lifetime and low particle release are achieved.

Benefits of technology

It achieves a plasma resistance lifespan of sealing materials that is more than doubled, a particle release rate that is reduced by an order of magnitude, a significant cost reduction, meets high cleanliness requirements, and is easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of radiation-resistant sealing materials for photoetching process and preparation method thereof, belong to high molecular sealing material technical field.The material is made of fluorine rubber raw rubber, 1-iodine perfluorohexane or 1-iodine perfluorooctane, reinforcing filler, bisphenol AF vulcanizing agent and benzyl triphenyl phosphonium chloride accelerator, etc.According to specific weight part, it is made by batch dropwise mixing and gradual temperature two-step vulcanization.The application utilizes perfluoroalkyl iodide under plasma C-I bond preferentially homolysis generates I·, terminates fluorine rubber free radical chain degradation;And through theoretical calculation and ion chromatography verification, ensure that processing process does not decompose, no corrosive iodine ion release in service.The application breaks the application technology prejudice of halogen, solves the defect that conventional fluorine rubber particle releases high, plasma life is short, avoids the problem that perfluoroether rubber is high in cost and difficult to process, the obtained material is low in particle release amount, long in radiation life, small in compression permanent deformation, adapts to 7nm and below node semiconductor equipment sealing demand, easy to scale up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer sealing materials technology, specifically relating to a radiation-resistant sealing material for photolithography and its preparation method. Background Technology

[0002] In dry plasma etching and EUV lithography auxiliary equipment for advanced semiconductor processes at 7nm and below, vacuum dynamic sealing materials must withstand the combined effects of high-energy plasma (such as CF4, O2, SF6, etc.), ultraviolet radiation, and highly corrosive gases for extended periods. Any particle release or premature failure of the seal will directly lead to wafer contamination and reduced yield, thus imposing extremely stringent requirements on the material's radiation resistance, low particle release, and chemical stability.

[0003] While conventional fluororubber (FKM) possesses excellent resistance to chemical media, its core failure mechanism under the aforementioned conditions is the breakage of the polymer backbone caused by high-energy radiation, generating primary free radicals (·F, ·CF2, etc.), which in turn trigger a self-accelerating chain degradation reaction, resulting in rapid surface etching, crack propagation, and the release of a large number of nanoscale particles. Existing countermeasures mostly employ passive protection: adding radiation-absorbing fillers such as nano-CeO2 and Y2O3 can only capture some primary free radicals and cannot interrupt the already initiated chain degradation; surface coating modification may lead to secondary particle contamination due to coating peeling. Currently, the only material that can meet the sealing requirements for nodes below 7nm is perfluoroether rubber (FFKM), but it relies on a perfluorinated molecular chain design, costing 5-10 times more than conventional FKM, and is difficult to process, hindering its large-scale application.

[0004] Furthermore, the semiconductor industry generally implements extremely strict controls on the halogen content in sealing materials, believing that halogen compounds decompose in a plasma environment to produce corrosive volatiles such as HI and I2, which can damage equipment and wafers. This technological bias effectively closes the door to actively introducing any halogen-containing compounds into high-cleanliness sealing materials.

[0005] Therefore, there is an urgent need for a new sealing material technology that addresses the root cause of free radical chain degradation, achieves inherent radiation resistance and low particle release, while also being cost-effective and easy to industrialize. Summary of the Invention

[0006] The purpose of this invention is to overcome existing technological biases and provide a radiation-resistant sealing material for photolithography processes based on an active protection mechanism of "free radical chain transfer termination". This material introduces a perfluoroalkyl iodide with a specific structure into a common fluororubber system. Under plasma radiation, it utilizes the preferential homolytic cleavage of CI bonds to release iodine radicals (I·), efficiently terminating the free radicals in the fluororubber chains, thereby achieving a qualitative leap in radiation resistance lifetime and particle release level.

[0007] To achieve the above objectives, the technical solution of the present invention has undergone extensive experiments and theoretical analysis to confirm the synergistic matching relationship between the components and processes, as detailed below.

[0008] This invention provides a radiation-resistant sealing material for photo-etching processes, which is made from a compound containing the following raw materials in parts by weight through a specific vulcanization process: 100 parts of fluororubber raw rubber; 1-4 parts of perfluoroalkyl iodide; 20-30 parts of reinforcing filler; 5-15 parts of acid absorber; 1.5-4 parts of vulcanizing agent; and 0.5-2 parts of vulcanization accelerator. The perfluoroalkyl iodide is 1-iodoperfluorohexane (C6F... 13 I) or 1-iodoperfluorooctane (C8F) 17 At least one of (I) is used, wherein the vulcanizing agent is bisphenol AF and the vulcanization accelerator is benzyltriphenylphosphine chloride (BPP). Meanwhile, in the preparation of the compound, the perfluoroalkyl iodide needs to be added in batches; during the second-stage vulcanization, a gradual heating method is used to raise the temperature to 230-250°C at a rate of 5-10°C / h, followed by holding at that temperature.

[0009] In the above scheme, the use of C6-C8 perfluoroalkyl iodides is key to achieving the core function of this invention. The inventors have confirmed through density functional theory (DFT) calculations that C6F... 13 The dissociation energy of the CI bond of I is approximately 235 kJ / mol, far lower than that of the CC bond (approximately 348 kJ / mol) and CF bond (approximately 485 kJ / mol) in the fluororubber main chain. Under the influence of plasma radiation energy, the CI bond will preferentially undergo homolytic cleavage, selectively generating I·, rather than the main chain breaking randomly. The generated I· rapidly combines with fluororubber chain radicals to form stable CI end groups, thereby terminating the chain degradation. If the carbon chain length is below C6, the compatibility with the fluororubber matrix decreases significantly, and the boiling point is low, making it difficult to remain stably in the matrix during processing and use; if it is above C8, the dispersion uniformity is limited, and the chain transfer efficiency no longer improves. A dosage range of 1-4 parts can sufficiently ensure the supply of I· to quench a large number of chain radicals, while avoiding excessive amounts that may lead to deterioration of the material's mechanical properties or possible exudation.

[0010] The combination of bisphenol A (AF) vulcanization system and BPP accelerator not only imparts excellent chemical resistance and low compression set to fluororubber, but also exhibits a mild reaction process, avoiding side reactions of the CI bonds or the generation of interfering free radicals during vulcanization. This ensures the chemical integrity and subsequent chain transfer activity of the perfluoroalkyl iodide. In contrast, the peroxide vulcanization system generates a large number of reactive free radicals during vulcanization, which can undergo non-productive reactions with the perfluoroalkyl iodide, thereby weakening its plasma protection capability.

[0011] To address the concerns of those skilled in the art regarding "decomposition of iodides at high temperatures" and "generation of corrosive volatiles," this invention provides a solid theoretical basis, thermal analysis experimental data, and process assurance.

[0012] Theoretically, based on the Arrhenius formula, for a CI bond with a bond energy of about 235 kJ / mol, the thermal homolytic half-life at 240 °C (513 K) is as long as several decades, far exceeding the two-stage sulfidation time of several hours. Therefore, the perfluoroalkyl iodide itself hardly undergoes thermal decomposition during the sulfidation process.

[0013] From an experimental perspective, the applicant used thermogravimetric analysis (TGA) to verify the thermal stability of the compound containing perfluoroalkyl iodides. The test conditions were a nitrogen atmosphere, with the temperature increased from room temperature to 250°C at a rate of 5°C / min. The results showed that within the 70-100°C range (corresponding to the two-stage mixing temperature range), the sample weight loss was less than 0.5%, mainly attributed to the removal of trace amounts of adsorbed moisture. Within the 170-240°C range (corresponding to the vulcanization temperature range), apart from the volatilization of a small amount of low-molecular-weight compounds inherent in the vulcanization reaction of fluororubber, no characteristic weight loss step corresponding to the thermal decomposition of perfluoroalkyl iodides was observed. In stark contrast, the control sample using C4F9I (boiling point 82°C) showed a significant weight loss step in the 80-110°C range, with a weight loss rate of 8.2%, consistent with its boiling point, confirming that a large amount of short-chain perfluoroalkyl iodides had already volatilized and been lost at the processing temperature. The aforementioned TGA data, along with reproducible experimental evidence, demonstrate that the C6-C8 perfluoroalkyl iodides selected in this invention possess sufficient thermal stability within the process temperature range employed in this invention and will not lose their function due to thermal decomposition or volatilization.

[0014] Meanwhile, the selected perfluoroalkyl iodides all have boiling points above 140℃, and the batch-droplet addition and gradual heating process design further suppresses volatilization losses during processing. In the plasma service environment, the I· generated by the preferential radiative dissociation of CI bonds is efficiently captured in situ by macromolecular chain free radicals, anchored covalently to the end groups of the fluororubber network, and fixed in the matrix by the subsequent high-temperature vacuum degassing process, thus preventing its conversion into free I2 or HI. Through extensive experimental verification, the applicant, using ultra-trace analysis methods in the semiconductor industry, found no iodine ions exceeding background levels (IC detection limit <0.01ppb) in the post-exposure cleaning solution collected under simulated plasma conditions, thus completely breaking the technical prejudice that "halogens inevitably produce corrosive contamination."

[0015] As a further optimization, the raw materials selectively include 0-10 parts of an auxiliary free radical scavenger, preferably nano-CeO2 or nano-Y2O3 with a particle size of 20-100 nm. The auxiliary scavenger can remove some primary free radicals, forming a dual synergistic protection mechanism of "source inhibition + process termination" with perfluoroalkyl iodides, further extending radiation resistance lifetime without introducing additional particle release risks. The fluororubber raw material is preferably an industrially mature type 26 or 246 vinylidene fluoride-hexafluoropropylene copolymer, and the reinforcing filler is preferably one or a mixture of MT carbon black and fumed silica, both exhibiting excellent compatibility with perfluoroalkyl iodides.

[0016] This invention also provides a method for preparing the sealing material, mainly comprising: plasticizing, first-stage mixing with filler and acid scavenger, second-stage batch-drop addition of perfluoroalkyl iodide at high temperature, third-stage cooling followed by thin-pass vulcanization, first-stage compression vulcanization, second-stage progressive heating oven vulcanization, and vacuum degassing. The batch-drop addition process ensures uniform molecular-level dispersion of the perfluoroalkyl iodide in the matrix, avoiding excessively high local concentrations; the progressive heating vulcanization provides sufficient time for perfecting the cross-linking structure and achieving deep compatibility between the perfluoroalkyl iodide and the matrix; and finally, vacuum degassing further removes trace amounts of volatile residues. The entire process is based entirely on general-purpose rubber processing equipment, requiring no special modifications and easily scalable for mass production.

[0017] The present invention has the following advantages over the prior art: (1) For the first time, perfluoroalkyl iodides were introduced as free radical chain transfer terminators into ordinary fluororubber. Through precise bond energy matching and compatibility design, active protection against plasma-induced chain degradation was achieved from the root. The plasma resistance life was increased by more than 2 times compared with unmodified FKM, and the particle release was reduced by an order of magnitude.

[0018] (2) Through DFT theoretical calculation and TGA thermal analysis experiment, it was confirmed that perfluoroalkyl iodides have sufficient thermal stability at the sulfidation temperature, and it was also confirmed that they are fixed in the form of covalent bonds after plasma treatment, without producing corrosive free halogens, thus breaking industry prejudice and meeting the requirements of high cleanliness.

[0019] (3) Using cheap and readily available ordinary fluororubber and a small amount of commercially available perfluoroalkyl iodide as raw materials, and adopting traditional mixing and vulcanization equipment, the cost is much lower than that of perfluoroether rubber, and the process is simple and controllable. It perfectly solves the core contradiction between high performance and high cost, and high cleanliness and easy industrialization, and has broad application prospects. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1 1) Plasticizing: Put 100 parts by weight of 246 type fluororubber raw rubber into an internal mixer and plasticize for 10 minutes until it completely covers the rollers.

[0022] 2) First stage of mixing: Add 8 parts by weight of magnesium oxide, 4 parts by weight of calcium hydroxide and 25 parts by weight of MT carbon black, and mix for 15 minutes until evenly dispersed.

[0023] 3) Two-stage mixing: Take 3 parts by weight of 1-iodoperfluorohexane (C6F) 13 I (purity > 99%), added in 3 drops, 1 part each time, and mixed for 4 minutes after each drop, controlling the mixing temperature at 70-90℃, for a total mixing time of 25 minutes.

[0024] 4) Three-stage mixing: Cool the rubber compound to below 50°C, add 2.5 parts by weight of bisphenol AF, 1 part by weight of benzyltriphenylphosphine chloride (BPP) and 1 part by weight of calcium stearate, pass through the thin sheet 10 times and then cool it.

[0025] 5) First stage vulcanization: vulcanize for 15 minutes at 175℃ and 20MPa on a molding press.

[0026] 6) Second-stage vulcanization and post-treatment: Place in an oven and heat to 240°C at a rate of 8°C / h, and keep at that temperature for 12 hours; then transfer to a vacuum oven and degas at 140°C for 3 hours to obtain the sealing material.

[0027] Example 2 In the "single-stage mixing" step of Example 1, an additional 8 parts by weight of nano CeO2 (average particle size 50 nm) were added and mixed with the filler and acid scavenger. The remaining steps and raw materials were exactly the same as in Example 1.

[0028] Example 3 Replace the fluororubber raw rubber with 100 parts by weight of type 26 fluororubber, change the reinforcing filler to 20 parts by weight of fumed silica, and add 2 parts by weight of 1-iodoperfluorooctane (C8F) to the two-stage mixing process. 17 I), and the same batch dripping and gradual temperature increase vulcanization procedure as in Example 1 was adopted. The vulcanizing agent and accelerator were adjusted to 2 parts by weight of bisphenol AF and 0.8 parts by weight of BPP. The rest were the same as in Example 1.

[0029] Example 4 The same formulation as in Example 1 was used, but in the two-stage mixing, 3 parts by weight of 1-iodoperfluorohexane were added all at once instead of being added dropwise; during the two-stage vulcanization, the oven was directly heated to 240°C before the product was placed in and kept at that temperature, instead of using a gradual heating method. The purpose was to compare the effects of process conditions.

[0030] Comparative Example 1 No perfluoroalkyl iodides were added, and the remaining steps were the same as in Example 1.

[0031] Comparative Example 2 The perfluoroalkyl iodide in Example 1 was replaced with an equal amount of hindered phenolic antioxidant (brand name 1010), and the rest were the same.

[0032] Comparative Example 3 The 1-iodoperfluorohexane in Example 1 was replaced with an equal amount of 1-iodoperfluorobutane (C4F9I, boiling point 82°C), and the rest were the same.

[0033] Comparative Example 4 The vulcanization system was replaced with 2 parts by weight of dicumyl peroxide (DCP) and 3 parts by weight of triallyl isocyanurate (TAIC), and the first-stage vulcanization temperature was adjusted accordingly to 165°C. The remaining formulation and batch / gradual process were the same as in Example 1.

[0034] Comparative Example 5 The system adopts a combination of one-time feeding, direct heating two-stage vulcanization, and peroxide vulcanization system, with the rest of the basic formula being the same as in Example 1.

[0035] Performance verification 1. Particle Release Rate: Referring to SEMI F21-0701 standard, O-rings of Φ20×2mm were fabricated from each material sample and installed on a dynamic sealing test bench. A CF4 / O2 / SF6 (volume ratio 3:1:1) mixture was introduced and maintained at 200℃, 0.1MPa, and a dynamic friction rate of 5mm / s for 24 hours. The number of particles ≥0.1μm was measured using a laser particle counter, expressed as particles / cm². 2 count.

[0036] 2. Plasma resistance lifetime: Place the sample in a plasma etching machine with a power of 300W, the same gas atmosphere as before, and a temperature of 200℃, and continue to expose it until the tensile strength drops to 50% of the initial value. Record the exposure time.

[0037] 3. Etching rate: After 100 hours of exposure, the average thickness loss was measured, and the etching rate per unit time (μm / h) was calculated.

[0038] 4. Compression set: According to GB / T 7759-2015, 175℃×70h, 25% compression ratio.

[0039] 5. Thermal stability: Take about 10mg of each sample of pre-vulcanized compound rubber and use a thermogravimetric analyzer under a nitrogen atmosphere to heat from room temperature to 250℃ at a heating rate of 5℃ / min. Record the cumulative weight loss in the 70-100℃ range and the 170-240℃ range.

[0040] 6. Volatile Corrosion Products: After exposing the samples of the examples and comparative examples to the plasma for 100 hours, the surface deposits were ultrasonically extracted with ultrapure water at 50°C for 1 hour. The iodide ion concentration in the extract was analyzed by ion chromatography. - Concentration (detection limit 0.01 ppb).

[0041] The test results are shown in Table 1.

[0042] Table 1 Performance Test Results

[0043] As shown in Table 1, in Examples 1-3, which used the specific perfluoroalkyl iodide of this invention in conjunction with a batch dripping and progressive vulcanization process, the particle release was all below 20 particles / cm³. 2 It has a plasma resistance life of over 1000 hours, an etching rate of less than 3μm / h, small compression set, and a volatile iodine ion concentration that is always below the instrument detection limit, fully meeting the sealing cleanliness and lifespan requirements of semiconductor equipment at 7nm and below nodes.

[0044] Based on the thermal stability data, Examples 1-3 showed weight loss rates below 0.5% in the mixing temperature range of 70-100℃ and only 1.0-1.2% in the vulcanization temperature range of 170-240℃. After deducting the inherent low-molecular-weight volatilization of fluororubber, no characteristic weight loss corresponding to the thermal decomposition of perfluoroalkyl iodides was observed, confirming that the C6-C8 perfluoroalkyl iodides selected in this invention have sufficient thermal stability throughout the process. In contrast, Comparative Example 3, using C4F9I, showed a significant weight loss of up to 8.2% in the 70-100℃ range and a further weight loss of 5.6% in the 170-240℃ range. This is consistent with the characteristics of C4F9I, which has a low boiling point and significant volatilization during processing. This also directly explains why its particle release and lifespan performance are far inferior to those of the Examples.

[0045] In Example 4, due to the use of single-feeding and direct heating, the perfluoroalkyl iodide was unevenly dispersed and experienced slight volatilization loss during sulfidation. The weight loss rate in the 170-240°C range increased to 2.8%, higher than the 1.2% in Example 1, resulting in an increase in particle release to 42 particles / cm³. 2The lifetime decreased to 680 hours, but it was still significantly better than Comparative Example 1 without the addition of perfluoroalkyl iodides. This confirms the necessity of batch addition and gradual temperature increase processes for suppressing RF-I volatilization loss and maximizing material performance.

[0046] Comparative Example 1 shows that ordinary fluororubber without any chain terminator degrades rapidly under plasma. Comparative Example 2, using a traditional free radical inhibitor, failed to effectively interrupt the chain reaction, resulting in limited improvement. Comparative Example 3, using C4F9I with an excessively short carbon chain and low boiling point, showed minimal performance improvement due to significant volatilization losses during processing (directly confirmed by TGA data) and poor compatibility in use. Furthermore, it produced measurable iodide ion release, demonstrating the unique advantages of perfluoroalkyl iodides with C6 or higher carbon chains. Comparative Examples 4 and 5 show that the peroxide vulcanization system reacts adversely with perfluoroalkyl iodides, weakening the protective effect. The weight loss rate in the 170-240°C range was also higher than in the examples (2.3% and 3.1%, respectively). Additionally, due to vulcanization byproducts and the acidic environment, iodide ion release was slightly increased, highlighting the synergistic compatibility between the bisphenol AF / BPP vulcanization system and the present invention.

[0047] In summary, the sealing material and its preparation method provided by this invention, through the synergistic effect of various technical features, have achieved a breakthrough in comprehensive performance, possessing outstanding substantive characteristics and significant progress.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A radiation-resistant sealing material for photolithography, characterized in that, Made by vulcanization of a compound rubber comprising the following parts by weight of raw materials: 100 parts of fluororubber raw rubber; 1-4 parts of perfluoroalkyl iodide; 20-30 parts of reinforcing filler; 5-15 parts of acid absorbent; 1.5-4 parts vulcanizing agent; Vulcanization accelerator 0.5-2 parts; The perfluoroalkyl iodide is at least one of 1-iodoperfluorohexane and 1-iodoperfluorooctane; The vulcanizing agent is bisphenol AF, and the vulcanization accelerator is benzyltriphenylphosphine chloride; Furthermore, during the preparation of the compound, the perfluoroalkyl iodide is added in batches, and the compound is mixed for 3-5 minutes after each addition; and during the two-stage vulcanization of the compound, a gradual heating method is adopted, with the temperature increased at a rate of 5-10℃ / h to 230-250℃ and then held at that temperature.

2. The sealing material according to claim 1, characterized in that, The raw materials also include 0-10 parts of an auxiliary free radical scavenger, which is nano CeO2 or nano Y2O3 with a particle size of 20-100 nm.

3. The sealing material according to claim 1, characterized in that, The fluororubber raw material is selected from type 26 or type 246 vinylidene fluoride-hexafluoropropylene copolymer.

4. The sealing material according to claim 1, characterized in that, The reinforcing filler is selected from one or a mixture of two of MT carbon black and fumed silica.

5. A method for preparing the sealing material according to any one of claims 1-4, characterized in that, Includes the following steps: 1) Plasticize the raw fluororubber in a two-roll mill or internal mixer for 5-15 minutes; 2) Add acid absorber and reinforcing filler to the plasticized fluororubber and mix for 10-20 minutes; 3) Slowly add perfluoroalkyl iodide in batches, mixing for 3-5 minutes after each addition before adding the next batch. Mix at 70-100℃ for 15-30 minutes. 4) Cool to below 60℃, add vulcanization accelerator and vulcanizing agent, and pass through a thin sheet 8-12 times before unloading; 5) Perform a compression molding vulcanization on the compound rubber at 170-180℃, 10-30MPa, for 10-20min; 6) After vulcanization in a two-stage oven, the temperature is gradually increased to 230-250℃ at a rate of 5-10℃ / h, and then held for 6-24h. After vacuum degassing at 120-150℃ for 2-4h, the sealing material is obtained.